Facile Synthesis of Conductive Flexible Composite Sn@Ag Microspheres and their Application in Anisotropic Conductive Films (Part. Part. Syst. Charact. 1/2022). (14th January 2022) - Zhang, Wen Hua; Fan, Pei Yuan; Yu, Xianglei; Cheng, Jun Hua; Cheng, Ding Xiang; Liu, Cheng Bing; Gan, Guo You; Li, Jun Peng
Abstract : In article 2100161, Gan, Li, and co‐workers study the core‐shell structure composite conductive microsphere Sn@Ag, combined with resin, creates an anisotropic conductive film (ACF) with a flexible core. The reducibility of Sn is used to omit the preparation process of active sites, and the facile preparation of Sn@Ag is completed in one step. The proposed ACF can be deformed during the packaging process to reduce the uneven particle size problem and improve the conductivity.